Fractional control of cordinated manipulators - Ferreira, N. M. Fonseca (2019)
When two robots execute a coordinated motion it is required specification not only of the desired trajectory of each robot, but also of the forces exerted by the end effectors. This article discusses the fractional-order position and force control of two co-operative robots handling one object. The system robustness and performance is analyzed and compared with other control approaches. The experiments reveal that fractional algorithms lead to performances superior to classical integer-order controllers.